Duration of anaemia during the first week of life is an independent risk factor for retinopathy of prematurity. (11th January 2018) - Lundgren, Pia; Athikarisamy, Sam E.; Patole, Sanjay; Lam, Geoffrey C.; Smith, Lois E.; Simmer, Karen
Abstract: Aim: This study evaluated the correlation between retinopathy of prematurity (ROP), anaemia and blood transfusions in extremely preterm infants. Methods: We included 227 infants born below 28 weeks of gestation at King Edward Memorial Hospital, Perth, Australia, from 2014–2016. Birth characteristics and risk factors for ROP were retrieved, and anaemia and severe anaemia were defined as a haemoglobins of <110 g/L and <80 g/L, respectively. Logistic regression was used for the analysis. Results: Retinopathy of prematurity treatment was needed in 11% of cases and the mean number of blood transfusions (p < 0.01), and mean number of weeks of anaemia (p < 0.001) and of severe anaemia (p < 0.05), had positive associations with ROP cases warranting treatment. In the multivariate logistic regression analysis, the best‐fit model of risk factors included anaemic days during first week of life, with an odds ratio (OR) of 1.46% and 95% confidence interval (CI) of 1.16–1.83 (p < 0.05), sepsis during the first 4 weeks of life (OR 3.14, 95% CI 1.10–9.00, p < 0.05) and days of ventilation (OR 1.03, 95% CI 1.01–1.06, p < 0.05). Conclusion: The duration of anaemia during the first week of life was an independent risk factor for ROP warranting treatment and preventing early anaemia may decrease this risk. Abstract :